2010
DOI: 10.1074/jbc.r110.130419
|View full text |Cite
|
Sign up to set email alerts
|

Oxytetracycline Biosynthesis

Abstract: Oxytetracycline (OTC) is a broad-spectrum antibiotic that acts by inhibiting protein synthesis in bacteria. It is an important member of the bacterial aromatic polyketide family, which is a structurally diverse class of natural products. OTC is synthesized by a type II polyketide synthase that generates the poly-␤-ketone backbone through successive decarboxylative condensation of malonyl-CoA extender units, followed by modifications by cyclases, oxygenases, transferases, and additional tailoring enzymes. Genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(99 citation statements)
references
References 82 publications
0
96
0
2
Order By: Relevance
“…2). The TcmN-like cyclase participates in first-and second-ring cyclizations (27)(28)(29), whereas TcmI-, OxyN-, and TcmJ-like cyclases are thought to direct subsequent ring closures (5,30). All four of these categories share an evolutionary history with their clustered KS (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2). The TcmN-like cyclase participates in first-and second-ring cyclizations (27)(28)(29), whereas TcmI-, OxyN-, and TcmJ-like cyclases are thought to direct subsequent ring closures (5,30). All four of these categories share an evolutionary history with their clustered KS (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This gene is apparently regulated by a MarR-family transcriptional regulator, OxyTA1 (also known as OtrR) that might also respond to oxytetracycline (Fig. 4) (Petkovic et al, 2006;Perera and Grove, 2010; Pickens and Tang, 2010). While the proposed mechanism requires further investigation, this mode of regulation offers potential advantages for cells.…”
Section: Oxytetracyclinementioning
confidence: 99%
“…The role of the acyl-CoA-ligase SsfL2, homologous to OxyH from the oxy gene cluster, putatively involved in the formation of the fourth ring of the TC-like compound SF2527 was discussed by Pickens et al (71). Interestingly, the OxyH was demonstrated by gene-inactivation studies to be dispensable: therefore, its function is not yet understood (4). Considering that the cyclisation steps in TC biosynthesis occur between enzymatically catalysed reactions and spontaneous chemically-driven reactions, it is not surprising that the mechanism of cyclisation is not yet fully understood.…”
Section: Formation Of the Tetracycline Backbone In Otc Biosynthesismentioning
confidence: 99%
“…The lower peripheral region, which extends from C10 to C4a, is involved in the interaction with the 30S ribosomal subunit via the oxygen functional groups on carbon atoms C10--C1, and the C2 amide functionality (2). It has been demonstrated that most modifi cations along the lower peripheral region of TC greatly decrease antimicrobial activity, whereas derivatives modifi ed along the upper peripheral region, particularly on positions C7-C9, have demonstrated greater activity against many diff erent biological targets (2,4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation